الحق في المحاكمة العادلة أثناء النزاعات المسلحة - جمال, ونوقي (My University, 2022)
عتبر الحق في المحاكمة العادلة من أهم الحقوق القضائية التي يتمتع بها الإنسان، وهي تشمل مجموعة من الضوابط الموضوعية والإجرائية التي يتعين الالتزام بها قبل أو أثناء المحاكمات سواء كانت مدنية أو جزائية، وتكمن أهمية الحق في المحاكمة العادلة في كونه ضمانة أساسية للحقوق والحريات العامة، ووسيلة لمنع الإساءة في استعمال السلطة خارج الأهداف المشروعة المقررة لها. وإذا كان الحق في المحاكمة العادلة واجبا مفروضا في أوقات السلم، فإنه أهميته تزداد أكثر خلال النزاعات المسلحة، نظرا للظروف الاستثنائية المحيطة بالمحاكمة، وطبيعة الأشخاص الخاضعين لها، وحالة العداء بين الدول والجماعات المسلحة التي تنجم عن النزاع المسلح، سواء كان دوليا أو داخليا، مما يجعل الاهتمام بهذا الحق ضرورة قصوى في النزاعات المسلحة، وهو الأمر الذي عالجه القانون الدولي الإنساني خاصة ضمن اتفاقيات جنيف لعام 1949 والبرتوكولين الإضافيين لعام 1977.The right to a fair trial is considered one of the most important judicial rights that a person enjoys, and it includes a set of substantive and procedural controls that must be adhered to before or during trials, whether civil or criminal. To prevent the abuse of power outside the legitimate objectives established for it. And if the right to a fair trial is an obligation imposed in times of peace, then its importance increases even more during armed conflicts, given the exceptional circumstances surrounding the trial, the nature of the persons subject to it, and the state of hostility between states and armed groups that result from armed conflict, whether it is international or internal, which makes Paying attention to this right makes it extremely necessary in armed conflicts, which is what international humanitarian law has dealt with, especially within the Geneva Conventions of 1949 and the Additional Protocols of 1977.
مجلد01 العدد 02
Keywords: لحق؛ المحاكمة؛ العادلة؛ النزاعات؛ المسلحة; catch up trial; fair; disputes; armed